某车液压助力转向系统动态特性的仿真 - 陈帆 (Jixie chuandong)
Aiming at researching the dynamic characteristics of a rack-and-pinion hydraulic power steering system,the mathematical models of the hydraulic system are established,which included conversion valve,steering hydraulic cylinder and other components.The dynamic characteristics of the system are simulated by using SIMULINK.The deflection angle emerged by the fluctuating load is taken as the input of the system,and the force of steering hydraulic cylinder is taken as the output.The results show that,the force of steering hydraulic cylinder increased when amplitude of deflection angle increased,and the force of steering hydraulic cylinder increased when frequency of deflection angle increased.In order to improve the dynamic characteristics of the hydraulic power steering system,torsion bar stiffness,the load mass and the effective fluid volumetric modulus of elasticity are analyzed.